Morbus Castleman in der rheumatologischen Praxis - Schmalzing, M.; Sander, O.; Seidl, M.; Marks, R.; Blank, N.; Kötter, I.; Tiemann, M.; Backhaus, M.; Manger, Bernhard; Hübel, K.; Müller-Ladner, U.; Henes, J. (Zeitschrift für Rheumatologie, 2023)
The term Castleman’s disease encompasses a group of rare lymphoproliferative diseases that show histopathological similarities in lymph node biopsy. Diagnostic criteria and a specific ICD-10 code have been available for a few years. Case studies listed at the beginning illustrate that close cooperation between clinicians and pathologists is required to enable a reliable diagnosis. For an optimal histopathological assessment, the pathologist is also dependent on the removal of a complete lymph node. Before distinguishing a potentially fatal multicentric idiopathic Castleman’s disease from the resectable unicentric form, which is important in terms of prognosis and treatment, early diagnosis presupposes that Castleman’s disease is considered in the differential diagnosis. Various immune phenomena and overlaps with autoimmune diseases can increase the probability of misdiagnosis or undetected cases in the clinical routine of rheumatologists. The intention of the present overview is therefore to point out the similarities with autoimmune diseases that are relevant for differential diagnoses and to point out situations that justify a review of the previous diagnosis.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Castleman’s disease; Histopathology; Idiopathic MCD; IL‑6; Lymph node hyperplasia